2024
DOI: 10.1186/s12984-024-01332-x
|View full text |Cite
|
Sign up to set email alerts
|

Extended reality to assess post-stroke manual dexterity: contrasts between the classic box and block test, immersive virtual reality with controllers, with hand-tracking, and mixed-reality tests

Gauthier Everard,
Quentin Burton,
Vincent Van de Sype
et al.

Abstract: Background Recent technological advancements present promising opportunities to enhance the frequency and objectivity of functional assessments, aligning with recent stroke rehabilitation guidelines. Within this framework, we designed and adapted different manual dexterity tests in extended reality (XR), using immersive virtual reality (VR) with controllers (BBT-VR-C), immersive VR with hand-tracking (BBT-VR-HT), and mixed-reality (MD-MR). Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Everard et al [ 3 14 ] reported comparable usability results, with SUS scores of 78 and 83 among healthy participants using a virtual BBT. At the time of this study, no additional results on the usability of digitized BBTs were available.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Everard et al [ 3 14 ] reported comparable usability results, with SUS scores of 78 and 83 among healthy participants using a virtual BBT. At the time of this study, no additional results on the usability of digitized BBTs were available.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, no studies have explored the clinical advantages of newly developed digital versions of the BBT using the dimensions proposed by Fawcett et al [23]. Everard et al reported comparable usability results with SUS scores of 78 [3] and 83 [14] among healthy subjects using a virtual BBT. At the time of this study, no additional results on the usability of digitized BBTs were available.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation